Electron microscopy study of carbides precipitated during destabilization and tempering heat treatments of 25 wt.%Cr-0.7 wt.%Mo high chromium cast irons. (April 2021) - Wiengmoon, Amporn; Pearce, John T.H.; Nusen, Sankum; Chairuangsri, Torranin
Graphical abstract: Highlights: Addition of 0.7 wt.%Mo promoted formation of secondary M23C6 carbide, instead of M7C3 Retained austenite has been found after destabilization heat treatment Ferrite and tempered M23C6 carbide found in the iron without Mo addition Decompositions of supersaturated martensite or retained austenite have been found after tempering heat treatment Abstract: The effect of a 0.7 wt.%Mo addition on the microstructure and hardness of a heat treated 25 wt.%Cr–2.4 wt.%C cast iron has been studied via comparison with a Mo free reference 25 wt.%Cr–2.4 wt.%C iron. Destabilization led to precipitation of M7 C3 and M23 C6 secondary carbides in the reference iron, whereas M23 C6 secondary carbide was found in the iron with 0.7 wt.%Mo. Tempering resulted in additional secondary carbide precipitation and formation of ferrite. Secondary hardening was found in the iron with 0.7 wt.%Mo. For the destabilized + tempered condition the macro-hardness of the iron with 0.7 wt.%Mo addition was higher than the reference iron due to a finer and denser distribution of secondary-carbides.